The Effect of the Poles Distances on Plasma Characteristic of Discharge Tube - Ali, N. H.; Yeser, M. A.; Ali, N. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effects of poles distances of a discharge tube (cathode and anode) were investigated. The distances(90,95,100,110,115,120,130,140)mm are considered. The influence of (25mT) parallel and (2mT) normal magnetic fields with respect to the discharge tube on electron temperature under a pressure of (6pascal) and (900volt) was studied by implementing double Langmuire probe into plasma. Curves fitting were performed to find the optimum values of electron temperature for all cases in this work.We found that the electron temperature as a function of poles distances is exponential form